Crisis Communication Strategies Of A State-Owned Enterprise: A Text Analysis Of News Portal Report During Mbz Elevated Toll Road Controversies - Ariel Pangihutan Ertanta Tarigan; Yohanes Thianika Budiarsa (Interaksi Online, 2026)
This research studies the crisis communication strategies that PT Jasa Marga Persero used during the time of crisis regarding MBZ Elevated Toll Road. Jasa Marga was faced with threats which are very harmful for their reputation because the issue is related to their infrastructure quality, technical failures, and corruption allegations. These crises put Jasa Marga in a high-responsibility context. This research uses a qualitative content analysis approach, analyzing crisis-related communications derived from official press releases and credible Indonesian online news platforms. Guiding the research approach, this research analyzed its data using Situational Crisis Communication Theory (SCCT) and Image Restoration Theory (IRT), supported by a coding matrix and meaning-making framework to interpret communication patterns, rhetorical strategies, and attribution of responsibility. Jasa Marga used a combination of SCCT, and IRT strategies in their crisis communication, depending on the nature of the crisis. Additionally, communication patterns reveal a tendency to shift blame, minimize severity, and emphasize institutional credibility through reminders of good governance practices. Jasa Marga also shows some limitations in maintaining a long-term trust. This is because there was an inconsistency in transparent communication and stakeholder engagement. This study contributes to the understanding of crisis communication in state-owned enterprises, particularly in infrastructure-related controversies in a digital public environment.